Exertional hypoxemia is more severe in fibrotic interstitial lung disease than in COPD. Issue 4 (28th November 2017) - Du Plessis, Jean P.; Fernandes, Senan; Jamal, Rakin; Camp, Pat; Johannson, Kerri; Schaeffer, Michele; Wilcox, Pearce G.; Guenette, Jordan A.; Ryerson, Christopher J.
ABSTRACT: Background and objective: Despite its clinical and prognostic significance, few studies have evaluated the severity of exertional oxygen desaturation in fibrotic interstitial lung disease (ILD). Our objectives were to identify clinical and physiological variables that predict the extent of exertional oxygen desaturation in fibrotic ILD and to quantify the severity of desaturation compared to chronic obstructive pulmonary disease (COPD). Methods: This retrospective study compared the results of 6‐min walk test (6MWT) performed while breathing room air in fibrotic ILD patients and COPD patients eligible for pulmonary rehabilitation. Outcomes included the oxygen saturation (SpO2 ) nadir and the change in SpO2 from rest during a 6MWT. Predictor variables were identified on unadjusted analysis, followed by multivariate analysis to identify independent predictors of desaturation. Results: The study included 134 patients with fibrotic ILD and 274 patients with COPD. The ILD and COPD cohorts had similar age, sex, frequency of major comorbidities, walk distance, baseline SpO2 and baseline Borg dyspnoea scores. DLCO was the strongest predictor of desaturation in both cohorts. Compared to patients with COPD, ILD patients had significantly lower SpO2 nadir values (88.1 ± 6.4 vs 91.0 ± 4.6) and greater decrease in SpO2 from baseline (7.4 ± 5.2 vs 4.5 ± 3.7) after adjusting for demographic features and pulmonary physiology ( P < 0.0005), with greater between‐group differences at lower DLCO values. Conclusion: Patients with fibrotic ILD have greater oxygen desaturation during 6MWT compared to patients with COPD when adjusting for demographic features and pulmonary physiology. These findings suggest the need for disease‐specific studies to evaluate the potential utility of ambulatory oxygen in fibrotic ILD. Abstract : See related Editorial Few studies have evaluated the severity of exertional hypoxemia in fibrotic interstitial lung disease (ILD). We demonstrate that exertional hypoxemia is more common and severe in fibrotic ILD compared to COPD. More ILD‐specific studies are needed to evaluate the potential utility of ambulatory oxygen in fibrotic ILD.